Evaluation of the collection of the Institute of Social Work and Community Development Library, University of the Philippines - Galang, Zenaida M., 1940-
Data gathering was done through documentary analysis, using mainly annual and other reports of the ISWCD and the ISWCD library, interviews, and a researcher-developed questionnaire to determine the perception of the eighteen faculty members of the ISWCD library collection.